Legal Analysis of Criminalization of Narcotics Abuse Perpetrators for Themselves Based on Justice (Study of Decision Number 116/Pid.Sus/2024/PN.Smg) - Wahyuningsih, Tri; Winjaya Laksana, Andri (Jurnal Hukum Khaira Ummah, 2025)
Abstract. Drug and illicit drug crimes are now transnational and carried out using sophisticated procedures and sophisticated technology. Law enforcement officers are expected to be able to prevent and overcome drug crimes in order to improve the morals and quality of Indonesian human resources as the next generation of this country. The use of narcotics if used without restrictions and medical supervision can endanger the health and even the lives of its users. As a country of law, Indonesia certainly has many regulations that govern social life. Narcotics Law Number 35 of 2009 has not regulated drug abuse. This was done as one of the important steps of the government to fulfill the contents of Article 4 of the 1945 Constitution, namely the protection of all Indonesian people, increasing public welfare, and protecting the people. Participation in the realization of a healthy national life, world order, eternal peace, and social justice. A case of drug abuse also occurred in the Semarang District Court area Number 116/Pid.Sus/2024/PN.Smg. Starting from the defendant together with witness ANGGA DWI PUTRA Bin ASOR HARIYANTO (who was submitted in a separate case file) on Thursday, January 4, 2024 at around 13.15 WIB or at least at another time in 2024, located on the side of Jalan Anggrek, Pekunden Village, Semarang Tengah District, Semarang City, or at least in another place that is still included in the jurisdiction of the Semarang District Court, attempted or conspiracy to commit a crime without rights or against the law offering for sale, selling, buying, receiving, acting as an intermediary in buying and selling, exchanging, or handing over Class I Narcotics, in the form of: 9 (nine) plastic clip packages, each of which was inserted into a yellow straw containing crystal powder of methamphetamine with a net weight of 2.23954 grams (two point two three nine five four grams) and 1 (one) plastic clip package containing crystal powder of methamphetamine with a net weight of 0.63632 grams (zero point six three six three two grams), wrapped in black plastic. On Thursday, January 4, 2024 at around 12.15 WIB when the defendant was at home, the defendant was contacted by Witness ANGGA DWI PUTRA via WA Chat, which in essence invited the defendant to accompany him to Simpang Lima in order to pick up crystal methamphetamine on the orders of MAULANA (DPO) with an unknown address and the defendant agreed.